More than just another bib: group dynamics in an elite nordic ski team - Cascagnette, J. C. W.; Benson, A. J.; Cruwys, T.; Haslam, S. A.; Bruner, M. W. (Journal of Sports Sciences, 2021)
The social environment within individual sport teams can have a significant influence on the success, development, and well-being of athletes. We explored elite individual sport athletes` group experiences through the lens of social identity theorising. Participants were six members (4 male, 2 female, Mage = 21.5 years) of a National Development Nordic Ski team. At two time points in the competitive season, we used Social Identity Mapping (Bentley et al., 2020) in combination with semi-structured interviews to explore athletes` experiences as a member of the ski team. Social Identity Mapping provided a visual representation of each participant`s social identities and was used to facilitate athletes` views of their group experiences in the semi-structured interviews. Interview data were thematically analysed to explicate participants` perceptions of social identity and cohesion, and their perceived relevance to success and development in elite individual sport. Major themes included social group memberships and identities, the presence of subgroups, the ebb and flow of cohesion and conflict, and teammate and coach influence on the group. On this basis, we argue that social identity mapping can be a valuable resource for athletes and coaches seeking to create a positive and cohesive team environment within an elite individual sport team.